Penerapan Prinsip Pengembangan Rencana Pelaksanaan Pembelajaran dan Silabus Aqidah Akhlaq dalam Pendidikan Madrasah - Keyzha Natania Azzahra Subagyo; Afiful Ikhwan (Journal Islamic Education, 2024)
This study aims to improve teachers' competence in developing syllabus and lesson plans through academic supervision and training workshops at primary and junior secondary school levels. The method used was School Action Research (SSR) in two cycles. Results showed significant improvement in teachers' skills. At the primary level, the percentage of syllabus completion increased from 52.63% in the first cycle to 89.47% in the second cycle, while the completion of lesson plan preparation increased from 36.82% to 89.47%. At the junior high school level, the gradual implementation of workshops also showed an increase in the quality of syllabus and lesson plan preparation from fair to very good, as well as increasing teacher activity and understanding in developing learning tools systematically. These results confirm that academic supervision and structured training can effectively improve the quality of teachers' lesson planning. Furthermore, education does not only aim to transfer knowledge, but also to form a whole individual who understands the psychosocial context, culture, and has piety, nationalism, and a strong personality. The educational process must be able to develop the potential of students in a sustainable manner, both intellectually, spiritually, socially and emotionally. Therefore, the role of teachers is crucial in designing a meaningful learning process. Without good planning and adequate teacher competence, holistic educational goals will not be achieved optimally.